2015
DOI: 10.1002/hed.24149
|View full text |Cite
|
Sign up to set email alerts
|

Potential relationship between Hashimoto's thyroiditis and BRAFV600E mutation status in papillary thyroid cancer

Abstract: Hashimoto's thyroiditis was negatively associated with BRAF(V600E) mutation, extrathyroidal extension, and lymph node metastasis. In addition, Hashimoto's thyroiditis was related to less lymph node metastasis and extrathyroidal extension in PTCs with BRAF(V600E) mutation. Therefore, Hashimoto's thyroiditis is a potentially protective factor in PTC. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1019-E1025, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
3
20
0
4
Order By: Relevance
“…Some studies have shown that HT is negatively associated with BRAF V600E mutation, extrathyroidal extension and lymph node metastasis. Moreover, even if there is a BRAF V600E mutation, HT can also inhibit the proliferation of thyroid and lymph node metastasis [9,10]. Our data support that HT is a protective factor of PTC.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Some studies have shown that HT is negatively associated with BRAF V600E mutation, extrathyroidal extension and lymph node metastasis. Moreover, even if there is a BRAF V600E mutation, HT can also inhibit the proliferation of thyroid and lymph node metastasis [9,10]. Our data support that HT is a protective factor of PTC.…”
Section: Discussionsupporting
confidence: 75%
“…Some studies have shown that HT may be a protective factor in PTC, and is negatively correlated with BRAF V600E mutation, extra thyroid proliferation and lymph node metastasis. Moreover, even if BRAF V600E is mutated, PTC patients accompanied with HT have less extrathyroidal extension and lymph node metastasis [9,10]. BRAF V600E mutation is the most common genetic variants of PTC.…”
mentioning
confidence: 99%
“…Relationship between Hashimoto's disease and RET-PTC chromosome translocation in PTC has long been discussed [6,62]. PTC with BRAF V600E , another important driver mutation in PTC, has been well known to be more aggressive than PTC without the mutation [63,64].…”
Section: Is Thyroid Autoimmunity Beneficial For or Harmful Against Thmentioning
confidence: 99%
“…PTC with BRAF V600E , another important driver mutation in PTC, has been well known to be more aggressive than PTC without the mutation [63,64]. In contrast to RET-PTC which is frequently associated with Hashimoto's thyroiditis, several studies show that the presence of BRAF V600E is negatively associated with lymphocyte infiltration, and is protective for aggressiveness of PTC [62,[65][66][67].…”
Section: Is Thyroid Autoimmunity Beneficial For or Harmful Against Thmentioning
confidence: 99%
“…Hashimoto's thyroiditis was negatively associated with BRAF V600E mutation, extrathyroidal extension in papillary carcinoma with BRAF V600E mutation. The conclusion is that Hashimoto's thyroiditis and lymphocytic infiltration of Hashimoto's thyroiditis are a potentially protective factor in papillary carcinoma against its progression, and it is independent of BRAF mutational status [43][44][45]. In a study, no BRAF or RAS mutations or RET-PTC rearrangements were identified in the dominant nodule in Hashimoto's thyroiditis [46].…”
mentioning
confidence: 93%